Spatiotemporal characteristics in the structure of jerk motion at female weightlifters according to anthropometric indexes. - Antonyuk O.V; Putsov S.O; Kononets B.V (Kharkov National Pedagogical University, 2011)
The features of technical preparedness are studied in the jerk of highly qualified female weightlifters with different body mass according to somatotype. The model values of spatiotemporal indices of motion structure in the jerk are determined. The analysis is conducted and differences are exposed in the biokinematics motion structure in competition exercise «jerk» of female athletes taking into account anthropometric indices in the different weight categories groups. In research took part the 116 strongest female weightlifters of the world.